2002
DOI: 10.1001/archinte.162.8.893
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sleep-Disordered Breathing in Community-Dwelling Adults<subtitle>The Sleep Heart Health Study</subtitle>

Abstract: A significant proportion of occult SDB in the general population would be missed if screening or case finding were based solely on increased body habitus or male sex. Breathing pauses and obesity may be particularly insensitive for identifying SDB in older people. A better understanding of predictive factors for SDB, particularly in older adults, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
752
19
34

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,181 publications
(867 citation statements)
references
References 31 publications
48
752
19
34
Order By: Relevance
“…Eleven percent of women and 25% of men aged 40 years or older have at least 15 apneas plus hypopneas per hour of sleep (apnea-hypopnea index, AHI). 1 OSA is associated with multiple adverse outcomes, including pathological daytime sleepiness, 2 a ~2-fold increase in motor vehicle accidents, 3 depression, 4 hypertension, 5 and all-cause mortality. 6 The main treatments include continuous positive airway pressure (CPAP), mandibular advancement splint devices, weight loss, and upper airway or bariatric surgery.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Eleven percent of women and 25% of men aged 40 years or older have at least 15 apneas plus hypopneas per hour of sleep (apnea-hypopnea index, AHI). 1 OSA is associated with multiple adverse outcomes, including pathological daytime sleepiness, 2 a ~2-fold increase in motor vehicle accidents, 3 depression, 4 hypertension, 5 and all-cause mortality. 6 The main treatments include continuous positive airway pressure (CPAP), mandibular advancement splint devices, weight loss, and upper airway or bariatric surgery.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…(43) Previously demonstrating that CPAP positively affected blood pressure in a sample that included sleepy participants,(35) the investigators suggested that the impact of CPAP on this outcome may be mechanistically related to daytime sleepiness. This possibility has implication for the treatment of sleep apnea in older adults where there is a higher prevalence of sleep disordered breathing in older compared to middle aged adults, (3,47) but who experience less daytime sleepiness. (4,48)…”
Section: Functional Status and Quality Of Lifementioning
confidence: 99%
“…It is characterized primarily by recurrent occlusion of the upper airway that results in oxyhemoglobin desaturation and periodic arousals from sleep (2). It now appears that even mild to moderate sleep apnea is associated with the development of hypertension, diabetes mellitus (3), and cardiovascular risk (4,5). With increasing obesity, sleep apnea can contribute to the development of daytime alveolar hypoventilation (obesity hypoventilation syndrome), cor pulmonale, and frank respiratory failure (6,7).…”
mentioning
confidence: 99%